Assessing the cost‐effectiveness of finding cases of hepatitis C infection in UK migrant populations and the value of further research. Issue 9 (11th November 2013) - Miners, A. H.; Martin, N. K.; Ghosh, A.; Hickman, M.; Vickerman, P.
summary Hepatitis C (HCV) infection can cause cirrhosis, liver cancer and death in the absence of treatment. Many people living in the UK but born overseas are believed to be infected with HCV although many are unlikely to know they are infected. The aim of this study is to assess the potential for a case‐finding approach to be cost‐effective and to estimate the value of further research. An economic evaluation and value of information analysis was undertaken by developing a model of HCV disease progression and by populating it with evidence from the published literature. They were performed from a UK National Health Services cost perspective, and outcomes were expressed in terms of quality‐adjusted life‐years (QALYs). The comparator intervention was defined as the background rate of testing (i.e. no intervention). The base case results generated an incremental cost‐effectiveness ratio (ICER) of about £23 200 per additional QALY. However, the ICER was shown to be particularly sensitive to HCV seroprevalence, the intervention effect / cost and the probability of treatment uptake. The value of information analysis suggested that approximately £4 million should be spent on further research. This evaluation demonstrates that testing UK migrants for HCV could be cost‐effective. However, further research, particularly to refine estimates of the probability of treatment uptake once identified, the utility associated with sustained virological response and the cost of the intervention, would help to increase the robustness of this conclusion.